Consumption status of functional drinks based on the theory of planned behavior and the stages of change model in female employees - Toorani, Azam; Moodi, Mitra; Zeinali, Tayebeh; Salmani, Fatemeh; Norozi, Ensiyeh (Scientific reports, 2024)
This study aimed to determine the consumption status of functional drinks based on the theory of planned behavior and the Stages of Change Model. This study was conducted on 536 female employees of Birjand offices in 2022. The data was collected by using the functional food questionnaire and was analyzed using SPSS with significance level of P < 0.05. The largest number of people consume probiotic drinks (buttermilk, kefir, etc.) were in the maintenance stages (31.2%) and who consume milk fortified with vitamin D were in the contemplation stage (37.3%). The mean score of the participants in the subscales of attitude, behavioral control, and subjective norm was 17.69 ± 3.05, 16.83 ± 2.88, 21.73 ± 4.33, respectively. The mean score of the attitude and subjective norm regarding the consumption of all drinks had a significant relation with the stages of change model ( p < 0.05). The results of this study showed that the most drinks that female employees consumed regularly were probiotic drinks, while they did not intend to use functional juices (pre-contemplation stage). Therefore, it seems that this theory can be used as a framework in designing educational programs in order to increase the consumption of functional foods and improve women's health.